Identification of factors that promote biogenesis of tRNACGASer. Issue 10 (3rd October 2018) - Xu, Fu; Zhou, Yang; Byström, Anders S.; Johansson, Marcus J.O.
ABSTRACT: A wide variety of factors are required for the conversion of pre-tRNA molecules into the mature tRNAs that function in translation. To identify factors influencing tRNA biogenesis, we previously performed a screen for strains carrying mutations that induce lethality when combined with a sup61-T47:2C allele, encoding a mutant form oft R N A C G A S e r . Analyzes of two complementation groups led to the identification of Tan1 as a protein involved in formation of the modified nucleoside N 4 -acetylcytidine (ac 4 C) in tRNA and Bud13 as a factor controlling the levels of ac 4 C by promoting TAN1 pre-mRNA splicing. Here, we describe the remaining complementation groups and show that they include strains with mutations in genes for known tRNA biogenesis factors that modify ( DUS2, MOD5 and TRM1 ), transport ( LOS1 ), or aminoacylate ( SES1 )t R N A C G A S e r . Other strains carried mutations in genes for factors involved in rRNA/mRNA synthesis ( RPA49, RRN3 and MOT1 ) or magnesium uptake ( ALR1 ). We show that mutations in not only DUS2, LOS1 and SES1 but also in RPA49, RRN3 and MOT1 cause a reduction in the levels of the alteredt R N A C G A S e r . These results indicate that Rpa49, Rrn3 and Mot1 directly or indirectly influencet R N A C G A S e r biogenesis.